M – C – M’ and the End of the ‘Transformation Problem’ - MOSELEY, FRED (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2016)
Abstract: The main reason for rejecting Marx’s theory over the last century has been the infamous ‘transformation problem’. The critics argue that in Marx’s theory of prices of production he ‘failed to transform the inputs’ of constant capital and variable capital from values to prices of production and thus Marx’s theory is logically incomplete and inconsistent. This paper argues that Marx did not ‘fail to transform the inputs’ because the inputs of constant capital and variable capital are not supposed to be transformed. Instead, constant capital and variable capital are supposed to be the same in the determination of both values and prices of production – the actual quantities of money capital advanced to purchase means of production and labor-power at the beginning of the circuit of money capital (M – C – M’) which are taken as given – and thus Marx’s theory of prices of production is logically coherent and complete. An algebraic summary of this “monetary” interpretation of Marx’s theory is presented in Section 3. And examples of the textual evidence to support this “monetary” interpretation are presented in Section 4.